Mechanically stable polymer networks incorporating polymeric ionic liquids for enhanced conductivity in solid-state electrolytes - Sezer Özenler; Nataliya Kiriy; Upenyu L. Muza; Martin Geisler; Anton Kiriy; Brigitte Voit (Designed Monomers and Polymers)
Enhancing both ionic conductivity and mechanical robustness remains a major challenge in designing solid-state electrolytes for lithium batteries. This work presents a novel approach in designing mechanically robust and highly conductive solid-state electrolytes, which involves ionic liquid-based cross-linked polymer networks incorporating polymeric ionic liquids (PILs). First, linear PILs with different side groups were synthesized for optimizing the structure. Molecular weights of the PIL samples, ranging from 30 to 40 kDa, were determined using a complimentary combination of thermal field-flow fractionation (ThFFF) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis. The aimed for networks were synthesized through the photo-initiated polymerization of a network-forming monomer and a cross-linker, in the presence of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and a PIL bearing quaternized imidazolium groups. The resulting cross-linked membranes – semi-interpenetrating networks – exhibit substantial mechanical strength, with a Young’s modulus of 40–50 MPa, surpassing the threshold for solid-state battery separators, while maintaining high ionic conductivity in the range of 4 × 10−4 S·cm−1 at 60°C. Notably, the introduction of oligo(ethylene glycol) moieties into the PIL structure significantly enhances ionic conductivity and allows for incorporation of a larger amount of the lithium salt compared to the alkyl-substituted analogs. Moreover, although cross-linking often impairs ionic transport as a result of restricted segmental mobility of the polymer chains, incorporation into the network of highly conductive linear PILs circumvents this issue. This unique combination of properties positions the developed membranes as promising candidates for application in solid-state lithium batteries, effectively addressing the traditional trade-off in electrolyte design.